Why do some emerging economies proactively accelerate the adoption of renewable energy? - Salim, Ruhul; Rafiq, S. (Elsevier, 2011)
This article analyses the determinants of renewable energy consumption in a panel of six major emerging economies, namely Brazil, China, India, Indonesia, Philippines and Turkey that are proactively accelerating the adoption of renewable energy. Using Fully modified ordinary least square (FMOLS), Dynamic ordinary least square (DOLS), and Granger causality methods this paper finds that in the long-run, renewable energy consumption is significantly determined by income and pollutant emission in Brazil, China, India and Indonesia while mainly by income in Philippines and Turkey. Causal link between renewable energy and income; and between renewable energy and pollutant emission are found to be bidirectional in the short-run. These results suggest that the appropriateness of the efforts undertaken by emerging countries to reduce the carbon intensity by increasing the energy efficiency and substantially increasing the share of renewable in the overall energy mix.